Where Strangers Become Neighbours Integrating Immigrants in Vancouver, Canada - Sandercock, Leonie; Attili, Giovanni (Urban and Landscape Perspectives, 2009)
In the present age of migration, the influx of immigrants from distant lands leads inevitably to the spatial and social restructuring of cities and regions. It is often accompanied by fears of and hostility towards the newcomers. Nevertheless, in Europe, North America and Japan this influx of immigrants is essential to economic growth. How can immigrants become accepted members of the society of their adopted country? How can strangers become neighbours? What alchemies of political and social imagination are required to achieve peaceful coexistence in the mongrel cities of the 21st century? What philosophies and policies have made integration successful in Canada and how can it be translated into European context? The book tackles an important contemporary issue - the social integration of immigrants in a large metropolis - by way of the detailed case study of one Canadian city. The book provides a large political and legal context which makes this case study comprehensible and inspiring to readers outside Canada. The accompanying award-winning film illustrates how one neighbourhood has been engaged in creating a welcoming place for everyone. The use of film-making as an action research tool and the digital ethnographic methodology provide alternative ways of understanding a complex social process. Leonie Sandercock is the author of ten books, the most recent include; Towards Cosmopolis: Planning for Multicultural Cities (1998) and Cosmopolis 2: Mongrel Cities of the 21st Century (2003). The latter book won the Paul Davidoff Award for best book awarded by the American Collegiate Schools of Planning. She also received the Dale Prize for Community Planning (2005), and the BMW Award for Intercultural Learning (2007), for her paper on 'Cosmopolitan Urbanism'. Giovanni Attili is an Urban Planning Research Fellow at the University of Rome (La Sapienza) and Postdoctoral Fellow at the University of British Columbia (UBC, Vancouver). He is recipient of the G. Ferraro Award for the best Urban Planning PhD Thesis in Italy in 2005. He is co-editor of the book, Storie di Città (Edizioni Interculturali, 2007) and author of the book, Rappresentare la città dei migranti (Jaca Book, 2008).